Inkjet Printing of Regenerated Silk Fibroin: From Printable Forms to Printable Functions. (16th June 2015) - Tao, Hu; Marelli, Benedetto; Yang, Miaomiao; An, Bo; Onses, M. Serdar; Rogers, John A.; Kaplan, David L.; Omenetto, Fiorenzo G.
<x xml:space="preserve">Abstract</x> A formulation of regenerated silk fibroin solution that can be easily functionalized and inkjet printed on numerous surfaces is developed. As an example, the inks can be printed on laboratory gloves that change color when exposed to bacteria.